MODULAR DESIGN AND ACTIVITIES OF STUDENTS IN THE FORMATION OF THEIR PROFESSIONAL AND RESEARCH COMPETENCIES. - Andrievsky Б.М. (Journal of Information Technologies in Education (ITE), 2013)
The article is devoted to coverage of the problems of using a modular design and technology training of students in creating their ability to research. Disclosed algorithm, organizational and pedagogical conditions for its implementation.